Editorial Note - Munga, Dr. Cosmas (Multidisciplinary Journal of Technical University of Mombasa, 2024)
We would like to thank all our authors and co-authors who contributed to the original scientific articles for the successful release of this 1st Issue of MJTUM Volume 3. This issue has a total of 5 original scientific research articles from a diverse array of fields ranging from chemical engineering, microbiology, mariculture, and social sciences. The content of all the articles is from dedicated research works from the authors and co-authors. MJTUM is hereby providing a platform to share the contents of these research works in contributing to knowledge dissemination to the scientific community and to all students in their quest to advance knowledge in their respective fields covered in this Volume 3 Issue 1. MJTUM will continue to give a platform for sharing of scientific findings of high quality to all our readers. It is my sincere hope that you will enjoy reading the wide coverage of these published articles covered in this issue as we prepare you for the release of Issue 2 of Volume 3 as soon as possible.